A laser measurement method for microscopic mechanical properties of material constituent phases
Through laser measurement methods, the correspondence between the microphase composition of metal structure materials and the macromechanical properties is established, which solves the problem of difficulty in detecting micromechanical properties in the prior art, and achieves broader applicability and lower light degree requirements.
Patent Information
- Application Number
- CN202210818954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-07-12
AI Technical Summary
The prior art is difficult to effectively detect the micromechanical properties of the microscopic phase composition in metal structural materials and establish a direct correspondence with the macroscopic mechanical properties of the material.
Through laser measurement method, the composition phase of the metal structure material to be detected is determined, and under different phase content ratios, a system of binary equations is established based on the mathematical relationship between the overall deformation depth of the surface of the metal structure material and the composition phase content. The overall deformation depth of different composition phases under the action of pulsed laser beam is obtained, thereby determining its micromechanical properties.
The test method is realized that directly reflects its macromechanical properties from the microphase composition of the material, making up for the lack of direct correspondence in the existing technology, has a wider scope of application and lower optical degree requirements.
Smart Images

Figure BDA0003741948860000041 
Figure BDA0003741948860000043 
Figure BDA0003741948860000044
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material analysis and testing, and in particular relates to a laser measurement method for microscopic mechanical properties of material constituent phases. Background Art
[0002] Metal structural materials usually have complex phase compositions, and metal materials with different phase compositions have different macroscopic mechanical properties. If the mechanical properties of different microscopic phases are obtained and then combined in different ways by mathematical recombination, it is expected that application materials with different macroscopic mechanical properties will be obtained. However, there is currently no testing method with high application value for the mechanical properties of different phases in metal structural materials.
[0003] The existing nanoindentation testing method directly tests the mechanical properties of tiny components of metal structural materials, but there is no direct correspondence between the nanohardness of tiny local areas of the material and the overall macroscopic mechanical performance of the material.
[0004] How to detect the micro-mechanical properties of the micro-phase composition in metal structural materials and make the obtained micro-mechanical properties play a decisive role in the design of the macro-performance of the materials has become a problem that technicians need to solve. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a laser measurement method for the microscopic mechanical properties of material constituent phases.
[0006] The technical solution of the present invention is:
[0007] A laser measurement method for microscopic mechanical properties of material constituent phases, comprising the steps of:
[0008] (1) Determine the composition phase of the metal structural material to be tested;
[0009] (2) Based on the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations was established to obtain the overall deformation depth of different constituent phases under the action of the pulsed laser beam.
[0010] (3) Determine the micromechanical properties of different component phases.
[0011] The micro-mechanical properties of the micro-phase composition do not refer to indicators that only represent the micro-scale mechanical properties of the material, but refer to the test performance of the phase composition that directly reflects the contribution of the phase composition to the overall macro-mechanical properties of the metal structural material. The present invention provides a typical example of the application of this concept: when a metal structural material M only includes phase A and phase B, the macro-mechanical properties of the metal structural material of a specific composition (including phase A and phase B at the same time) are m, and the micro-mechanical properties of phase A (equivalent to the metal structural material M1 with a phase B content of 0) are a, and the micro-mechanical properties of phase B (equivalent to the metal structural material M2 with a phase A content of 0) are b; the acquisition of m corresponds to the mathematical result determined by a and b based on the distribution of the content of phase A and phase B in a specific combination relationship; that is, the value of m changes with the change of the content ratio of phase A with micro-performance a to phase B with micro-mechanical performance b, and the value of the macro-mechanical property m is determined or determined based on the micro-mechanical properties a, micro-mechanical properties b, and the content ratio of phase A to phase B in the metal structural material.
[0012] Preferably according to the present invention, the metal structural material is isotropic, and the constituent phases inside the metal structural material are uniformly and randomly distributed in the test area, and there are no oriented organizational components such as texture; the constituent phases include matrix phase, precipitated phase, defects and components that affect the macroscopic mechanical properties of the metal structural material, and the macroscopic mechanical properties include elasticity, plasticity, stiffness, strength, hardness, impact toughness, fatigue strength and fracture toughness, etc.
[0013] Preferably, according to the present invention, in step (3), the micromechanical properties of the constituent phase correspond to the macromechanical properties of the metal structural material. If the macromechanical properties of the metal structural material are tested based on yield strength, the micromechanical properties of the constituent phase are defined as the yield strength of the constituent phase of the metal structural material. When the macromechanical properties of the metal structural material are tested based on other mechanical property indicators, the micromechanical property indicators of the constituent phase should be defined as the corresponding other macromechanical property indicators.
[0014] According to the preferred embodiment of the present invention, in step (2), when the constituent phases of the metal structural material to be tested are phase A and phase B, under different phase content ratios, a set of two-variable linear equations is established according to the mathematical relationship between the overall deformation depth of the surface of the metal structural material and the content of the constituent phases, and the overall deformation depths of phase A and phase B under the action of the pulsed laser beam are respectively obtained; the specific process is:
[0015] 2-1, assuming that when the constituent phases of the metal structural material are all phase A, the overall deformation depth of the metal structural material to be detected under the action of the pulsed laser beam is x; when the constituent phases of the metal structural material are all phase B, the overall deformation depth of the metal structural material to be detected under the action of the pulsed laser beam is y; wherein, the overall deformation depth is the maximum depth of the point-shaped pits formed on the surface of the material after the pulsed laser beam acts on the surface of the material; and the side length or diameter of the pulsed laser beam is not higher than 100 μm; the depth of the pits induced by the plastic deformation can be characterized and obtained by using a white light interferometer, a three-dimensional morphology characterization device, and other three-dimensional shape and size measurement devices.
[0016] 2-2, design two metal structural materials α and β to be tested with different A phase and B phase content ratios, that is, the number of phase content ratios of the designed metal structural materials to be tested is equal to the number of internal component phases of the metal structural materials to be tested;
[0017] 2-3, the metal structural materials α and β to be inspected are processed by a pulse laser beam, and the overall deformation depths of the metal structural materials α and β under the action of the pulse laser beam are obtained to be a and b respectively;
[0018] 2-4, respectively detecting the phase content ratio of phase A and phase B in metal structural materials α and β;
[0019] 2-5, under two different phase content ratios, according to the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations are established to obtain the overall deformation depths x and y of phase A and phase B under the action of the pulsed laser beam, respectively;
[0020] For example, when it is detected that the content ratio of phase A to phase B in the metal structural material α is 6:4, and the content ratio of phase A to phase B in the metal structural material β is 5:5, the established equation group is
[0021] In this step, the overall deformation depths of phase A and phase B under the action of the pulsed laser beam determined by the equation group are: x=5a-4b, y=6b-5a;
[0022] This step requires that the values of x and y are not negative numbers. If they are negative numbers, the present invention is not applicable to the micro-mechanical property test of different composition phases of the metal structural material to be tested.
[0023] Preferably, according to the present invention, in steps 2-4, the phase content ratio is obtained by microstructure detection methods such as optical microscopes and scanning electron microscopes, or by a composition phase revealing method based on the pulsed laser force effect. When the pulsed laser acts on the surface of certain materials with different phase compositions, and the laser beam action area can also completely cover several different phase structures, the laser shock will inevitably cause different composition phases on the material surface to present different degrees of deformation, and the difference in deformation degree makes the boundaries of different composition phases revealed, which also becomes a composition phase revealing method based on the pulsed laser force effect.
[0024] Preferably according to the present invention, in order to avoid ablation damage on the surface of the material to be measured, when the pulsed laser beam acts, the surface of the metal structure material to be measured is coated with an absorption layer, and the material of the absorption layer is black paint or black tape.
[0025] Preferably, according to the present invention, before the pulse laser beam acts, the surface of the metal structure material to be measured is subjected to a light finishing treatment, and the light finishing treatment method includes but is not limited to mechanical polishing, chemical polishing and the like;
[0026] Further preferably, the surface roughness of the material after the light-smoothing treatment is lower than Ra0.05. The basic physical basis of the laser measurement method of the present invention is the plastic deformation of the material components under the action of laser impact, and in order to more accurately characterize the deformation degree of different components, the surface of the material to be processed needs to maintain an excellent flat state and extremely low surface roughness.
[0027] According to the preferred embodiment of the present invention, in step (3), when the constituent phases of the metal structural material to be tested include phase A and phase B, the specific process of determining the micromechanical properties of phase A and phase B is as follows:
[0028] According to the fact that the degree of plastic deformation of metal structural materials is inversely proportional to the macroscopic mechanical properties, that is, the overall deformation depth of different metal structural materials under the action of laser shock pressure is inversely proportional to the macroscopic mechanical properties of the corresponding different metal structural materials, when the macroscopic mechanical properties of the metal structural material α to be tested are m, and when the macroscopic mechanical properties of the metal structural material β to be tested are n, then:
[0029]
[0030] In formula (I), z is a process parameter, and formula (I) yields
[0031] According to the overall deformation depth of the metal structure material α to be detected and the full A-phase metal structure material is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full A-phase metal structure material, the microscopic mechanical properties of the material component phase A are characterized by the macroscopic mechanical properties of the full A-phase metal structure material, then:
[0032]
[0033] In formula (II), p is the micromechanical property of phase A;
[0034] According to the overall deformation depth of the metal structure material α to be detected and the full B-phase metal structure material is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full B-phase metal structure material, the microscopic mechanical properties of the material component phase B are characterized by the macroscopic mechanical properties of the full B-phase metal structure material, then:
[0035]
[0036] In formula (III), q is the micromechanical property of phase B;
[0037] From formula (II) and formula (III), the micromechanical properties p of phase A are obtained:
[0038] From formula (II) and formula (III), the micromechanical properties q of phase B are obtained:
[0039] Based on the example in step (2) (x = 5a-4b, y = 6b-5a), we have From the above two formulas, we can get That is, the micromechanical properties of phase A and phase B in the example of step (2) are obtained.
[0040] The beneficial effects of the present invention are:
[0041] 1. The present invention makes up for the lack of intuitive measurement methods for micro-scale material composition phases, and provides a green laser measurement and characterization method for different mechanical properties of internal phase compositions of structural materials. Compared with existing nanoindentation measurement methods, the method of the present invention has a wider range of application occasions and lower requirements for the smoothness of the material to be tested.
[0042] 2. The material composition phase measurement method provided by the present invention more directly establishes the corresponding relationship between the microscopic mechanical properties and the macroscopic mechanical properties of the material, laying an experimental foundation for technicians to more thoroughly understand the quantitative relationship between material organization and performance. DETAILED DESCRIPTION
[0043] The present invention will be further described below with reference to the embodiments, but is not limited thereto.
[0044] Example 1
[0045] A laser measurement method for microscopic mechanical properties of material constituent phases, comprising the steps of:
[0046] (1) Determine the component phase of the metal structural material to be tested; specifically, it can be determined by microstructure detection methods such as optical microscopy and scanning electron microscopy;
[0047] Among them, the metal structural material is isotropic, and the constituent phases inside the metal structural material are uniformly and randomly distributed in the test area, and there are no oriented organizational components such as texture; the constituent phases include matrix phase, precipitated phase, defects and components that affect the macroscopic mechanical properties of the metal structural material, and the macroscopic mechanical properties include elasticity, plasticity, stiffness, strength, hardness, impact toughness, fatigue strength and fracture toughness, etc.
[0048] (2) Based on the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations was established to obtain the overall deformation depth of different constituent phases under the action of the pulsed laser beam.
[0049] (3) Determine the micromechanical properties of different component phases.
[0050] In step (3), the micromechanical properties of the constituent phase correspond to the macromechanical properties of the metal structural material. If the macromechanical properties of the metal structural material are tested based on yield strength, the micromechanical properties of the constituent phase are defined as the yield strength of the constituent phase of the metal structural material. When the macromechanical properties of the metal structural material are tested based on other mechanical properties, the micromechanical properties of the constituent phase should be defined as the corresponding other macromechanical properties.
[0051] The micro-mechanical properties of micro-phase composition do not refer to indicators that only represent the mechanical properties of materials at the microscopic scale, but rather to the test performance of phase composition that directly reflects the contribution of phase composition to the overall macroscopic mechanical properties of metal structural materials;
[0052] The present invention provides a typical example of the application of this concept: when a metal structural material M only includes phase A and phase B, the macroscopic mechanical property of the metal structural material with a specific composition (including phase A and phase B at the same time) is m, and the microscopic mechanical property of phase A (equivalent to metal structural material M1 with a phase B content of 0) is a, and the microscopic mechanical property of phase B (equivalent to metal structural material M2 with a phase A content of 0) is b; the acquisition of m corresponds to a mathematical result determined by a specific combination relationship of a and b based on the content distribution of phase A and phase B; that is, the value of m changes with the content ratio of phase A with microscopic property a to phase B with microscopic mechanical property b, and the value of the macroscopic mechanical property m is judged or determined based on the microscopic mechanical property a, the microscopic mechanical property b and the content ratio of phase A to phase B in the metal structural material.
[0053] Example 2
[0054] A laser measurement method for microscopic mechanical properties of material constituent phases, which differs from Example 1 in that:
[0055] In step (2), when the constituent phases of the metal structural material to be tested are phase A and phase B, under different phase content ratios, a set of two-variable linear equations is established according to the mathematical relationship between the overall deformation depth of the surface of the metal structural material and the content of the constituent phases, and the overall deformation depths of phase A and phase B under the action of the pulsed laser beam are respectively obtained; the specific process is:
[0056] In step (2), it is assumed that the technicians have built a pulsed laser surface impact treatment device and determined the laser impact process parameters, which include laser energy, pulse width, beam irradiation shape and area, and the absorption layer and constraint layer materials coated on the surface of the metal structure material to be measured.
[0057] 2-1, assuming that when the constituent phases of the metal structural material are all phase A, the overall deformation depth of the metal structural material to be detected under the action of the pulsed laser beam is x; when the constituent phases of the metal structural material are all phase B, the overall deformation depth of the metal structural material to be detected under the action of the pulsed laser beam is y; wherein, the overall deformation depth is the maximum depth of the point-shaped pits formed on the surface of the material after the pulsed beam acts on the surface of the material; and the side length or diameter of the pulsed beam is not higher than 100 μm; the depth of the pits induced by the plastic deformation can be characterized and obtained by using a white light interferometer, a three-dimensional morphology characterization device, and other three-dimensional shape and size measurement devices.
[0058] 2-2, design two metal structural materials α and β to be tested with different A phase and B phase content ratios, that is, the number of designed metal structural materials to be tested is equal to the number of internal component phases of the metal structural materials to be tested;
[0059] 2-3, the metal structural materials α and β to be inspected are processed by a pulse laser beam, and the overall deformation depths of the metal structural materials α and β under the action of the pulse laser beam are obtained to be a and b respectively;
[0060] 2-4, respectively detect the phase content ratio of phase A and phase B in the metal structural materials α and β; obtain the phase content ratio through microstructure detection methods such as optical microscopy and scanning electron microscopy, or obtain the phase content ratio through the composition phase exposure method based on the pulse laser force effect. When the pulse laser acts on the surface of certain materials with different phase compositions, and the laser beam action area can also completely cover several different phase structures, the laser shock will inevitably cause different composition phases on the material surface to present different deformation degrees, and the difference in deformation degree makes the boundaries of different composition phases revealed, which is also a composition phase exposure method based on the pulse laser force effect.
[0061] 2-5, under two different phase content ratios, according to the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations is established to obtain the overall deformation depths x and y of phase A and phase B under the action of the pulsed laser beam, respectively;
[0062] For example, when it is detected that the content ratio of phase A to phase B in the metal structural material α is 6:4, and the content ratio of phase A to phase B in the metal structural material β is 5:5, the established equation group is
[0063] In this step, the overall deformation depths of phase A and phase B under the action of the pulsed laser beam determined by the equation group are: x=5a-4b, y=6b-5a;
[0064] This step requires that the values of x and y are not negative numbers. If they are negative numbers, the present invention is not applicable to the micro-mechanical property test of different composition phases of the metal structural material to be tested.
[0065] In order to avoid ablation damage on the surface of the material to be measured, when the pulsed laser beam acts, the surface of the metal structure material to be measured is coated with an absorption layer, and the material of the absorption layer is black paint or black tape.
[0066] Before the pulsed laser beam acts, the surface of the metal structure material to be measured is subjected to a light finishing treatment, wherein the light finishing treatment method includes but is not limited to mechanical polishing, chemical polishing and the like;
[0067] The surface roughness of the material after light-smoothing treatment is lower than Ra0.05. The basic physical basis of the laser measurement method of the present invention is the plastic deformation of the material components under the action of laser impact. In order to more accurately characterize the deformation degree of different components, the surface of the material to be processed needs to maintain an excellent flat state and extremely low surface roughness.
[0068] In step (3), when the constituent phases of the metal structural material to be tested include phase A and phase B, the specific process of determining the micromechanical properties of phase A and phase B is as follows:
[0069] According to the fact that the degree of plastic deformation of metal structural materials is inversely proportional to the macroscopic mechanical properties, that is, the overall deformation depth of different metal structural materials under the action of laser shock pressure is inversely proportional to the macroscopic mechanical properties of the corresponding different metal structural materials, when the macroscopic mechanical properties of the metal structural material α to be tested are m, and when the macroscopic mechanical properties of the metal structural material β to be tested are n, then:
[0070]
[0071] In formula (I), z is a process parameter, and formula (I) yields
[0072] According to the overall deformation depth of the metal structure material α to be detected and the full A-phase metal structure material, which is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full A-phase metal structure material, and the microscopic mechanical properties of the material component phase A to which the present invention is directed are characterized by the macroscopic mechanical properties of the full A-phase metal structure material, then:
[0073]
[0074] In formula (II), p is the micromechanical property of phase A;
[0075] According to the overall deformation depth of the metal structure material α to be detected and the full B-phase metal structure material is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full B-phase metal structure material, the microscopic mechanical properties of the material component phase B are characterized by the macroscopic mechanical properties of the full B-phase metal structure material, then:
[0076]
[0077] In formula (III), q is the micromechanical property of phase B;
[0078] From formula (II) and formula (III), the micromechanical properties p of phase A are obtained:
[0079] From formula (II) and formula (III), the micromechanical properties q of phase B are obtained:
[0080] Based on the example in step (2) (x = 5a-4b, y = 6b-5a), we have From the above two formulas, we can get That is, the micromechanical properties of phase A and phase B in the example of step (2) are obtained.
[0081] Example 3
[0082] A laser measurement method for microscopic mechanical properties of material constituent phases, which differs from Example 2 in that:
[0083] (1) It was determined through testing that a certain nickel-based alloy is composed of γ′ phase and γ phase.
[0084] (2) A first nickel-based alloy with a γ′ phase to γ phase ratio of 6:4 and a second nickel-based alloy with a γ′ phase to γ phase ratio of 5:5 were designed, and an area without obvious defects such as pores and cracks was selected as the measurement area.
[0085] The material surface is smoothed by mechanical grinding and polishing until the surface roughness of the material is lower than Ra0.05. The overall deformation depth of the nickel-based alloy to be tested under the action of a specific pulsed laser beam is 10μm and 11μm, that is, a=10μm, b=11μm.
[0086] The laser energy was 6 J, the pulse width was 18 ns, the circular spot diameter was 3 mm, 3M tape was selected as the absorption layer material, and deionized water was selected as the constraint layer material.
[0087] According to the content ratio of phase A to phase B in the first nickel-based alloy being 6:4 and the content ratio of phase A to phase B in the second nickel-based alloy being 5:5, the established equation group is:
[0088] In this step, the overall deformation depths of the γ′ phase and the γ phase under the action of the pulsed laser beam determined by the equation group are x and y, respectively, and x and y satisfy: x = 5a-4b, y = 6b-5a;
[0089] The overall deformation depths of the full γ′ phase and the full γ phase are then obtained to be x=6 μm and y=16 μm, respectively.
[0090] In this embodiment, the yield strength of the material is used as a test basis to determine the microscopic mechanical properties of the γ′ phase and the γ phase in the metal structural material to be tested.
[0091] The yield strengths of the two nickel-based alloys with different contents of the above two components are 660 MPa and 600 MPa respectively, that is, m=660 MPa, n=600 MPa.
[0092] When the yield strengths of the metal structural materials α and β to be tested are m and n respectively, the micromechanical properties p of the γ′ phase and the micromechanical properties q of the γ phase are:
[0093] Depend on Conclusion Depend on Conclusion Depend on Conclusion
[0094] according to
[0095] The micromechanical properties of the γ′ phase and the γ phase were obtained to be 1100MPa and 412.5MPa, respectively.
[0096] The processes described in the present invention are all based on the example that the metal structural material to be detected includes only two different component phases. For the case where the metal structural material to be detected contains three or more different component phases, the technicians can adjust the calculation equation according to the actual situation, and then perform quantitative testing on the micromechanical properties of different component phases.
Claims
1. A laser measurement method for the microscopic mechanical properties of material components, characterized in that: Includes steps: (1) determining the constituent phases of the metal structural material to be tested; the metal structural material is isotropic, and the constituent phases inside the metal structural material are uniformly and randomly distributed in the test area, and there is no oriented structural component; (2) Under different phase content ratios, based on the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations is established to obtain the overall deformation depth of different constituent phases under the action of the pulsed laser beam. The specific process is as follows: 2-1, assuming that when the constituent phases of the metal structural material are all phase A, the overall deformation depth of the metal structural material to be detected under the action of the pulsed laser beam is x; When the constituent phases of the metal structure material are all B phases, the overall deformation depth of the metal structure material to be detected under the action of the pulsed laser beam is y; wherein the overall deformation depth is the maximum depth of the dot-shaped pits formed on the surface of the material after the pulsed laser beam acts on the surface of the material; 2-2, design two metal structural materials α and β to be tested with different A phase and B phase content ratios, that is, the number of phase content ratios of the designed metal structural materials to be tested is equal to the number of internal component phases of the metal structural materials to be tested; 2-3, the metal structural materials α and β to be inspected are processed by a pulse laser beam, and the overall deformation depths of the metal structural materials α and β under the action of the pulse laser beam are obtained to be a and b respectively; 2-4, respectively detecting the phase content ratio of phase A and phase B in metal structural materials α and β; 2-5, under two different phase content ratios, according to the mathematical relationship between the overall deformation depth of the metal structure material surface and the content of the constituent phases, a set of two-variable linear equations are established to obtain the overall deformation depths x and y of phase A and phase B under the action of the pulsed laser beam, respectively; (3) Determine the micromechanical properties of different constituent phases. When the constituent phases of the metal structural material to be tested include phase A and phase B, the specific process of determining the micromechanical properties of phase A and phase B is as follows: According to the fact that the degree of plastic deformation of metal structural materials is inversely proportional to the macroscopic mechanical properties, that is, the overall deformation depth of different metal structural materials under the action of laser shock pressure is inversely proportional to the macroscopic mechanical properties of the corresponding different metal structural materials, when the macroscopic mechanical properties of the metal structural material α to be tested are m, and when the macroscopic mechanical properties of the metal structural material β to be tested are n, then: In formula (I), z is a process parameter, and formula (I) yields According to the overall deformation depth of the metal structure material α to be detected and the full A-phase metal structure material is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full A-phase metal structure material, the microscopic mechanical properties of the material component phase A are characterized by the macroscopic mechanical properties of the full A-phase metal structure material, then: In formula (II), p is the micromechanical property of phase A; According to the overall deformation depth of the metal structure material α to be detected and the full B-phase metal structure material is inversely proportional to the macroscopic mechanical properties of the metal structure material α to be detected and the macroscopic mechanical properties of the full B-phase metal structure material, the microscopic mechanical properties of the material component phase B are characterized by the macroscopic mechanical properties of the full B-phase metal structure material, then: In formula (III), q is the micromechanical property of phase B; From formula (II) and formula (III), the micromechanical properties p of phase A are obtained: From formula (II) and formula (III), the micromechanical properties q of phase B are obtained:
2. A laser measurement method for microscopic mechanical properties of material components according to claim 1, characterized in that: The constituent phases include matrix phase, precipitated phase, defects and components that affect the macroscopic mechanical properties of metal structural materials. The macroscopic mechanical properties include elasticity, plasticity, stiffness, strength, hardness, impact toughness, fatigue strength and fracture toughness.
3. The laser measurement method for microscopic mechanical properties of material components according to claim 1, characterized in that: In step (3), the micromechanical properties of the constituent phase correspond to the macromechanical properties of the metal structural material. If the macromechanical properties of the metal structural material are tested based on yield strength, the micromechanical properties of the constituent phase are defined as the yield strength of the constituent phase of the metal structural material. When the macromechanical properties of the metal structural material are tested based on other mechanical properties, the micromechanical properties of the constituent phase should be defined as the corresponding other macromechanical properties.
4. The laser measurement method for microscopic mechanical properties of material components according to claim 1, characterized in that: In step (2), the side length or diameter of the pulsed laser beam is no greater than 100 μm.
5. The laser measurement method for microscopic mechanical properties of material components according to claim 4, characterized in that: In steps 2-4, the phase content ratio is obtained by optical microscopy, scanning electron microscopy, or a composition phase revealing method based on pulsed laser force effect.
6. The laser measurement method for microscopic mechanical properties of material constituent phases according to claim 1, characterized in that: When the pulsed laser beam acts, the surface of the metal structure material to be measured is coated with an absorption layer, and the material of the absorption layer is black paint or black tape.
7. The laser measurement method for microscopic mechanical properties of material constituent phases according to claim 1, characterized in that: Before the pulse laser beam acts, the surface of the metal structure material to be measured is subjected to a light finishing treatment, wherein the light finishing treatment method includes mechanical polishing and chemical polishing.
8. The laser measurement method for microscopic mechanical properties of material components according to claim 7, characterized in that: The surface roughness of the material after light finishing treatment is lower than Ra0.05.
Citation Information
Patent Citations
Method for determining target performance of low-carbon structure steel based on microscopic parameters of low-carbon structure steel
CN107367595A
Rock macroscopic fracture toughness calculation method based on nanoindentation technology
CN112364514A